2019
DOI: 10.1093/jac/dkz199
|View full text |Cite
|
Sign up to set email alerts
|

IncI1 ST3 and IncI1 ST7 plasmids from CTX-M-1-producing Escherichia coli obtained from patients with bloodstream infections are closely related to plasmids from E. coli of animal origin

Abstract: Objectives Fully sequenced IncI1 plasmids obtained from CTX-M-1-producing Escherichia coli of human and animal origin were compared. Methods Twelve E. coli isolates sharing identical ESBL genes and plasmid multilocus STs sequenced on Illumina and MinION platforms were obtained from the Danish antimicrobial resistance surveillance programme, DANMAP. After de novo assembly, the sequences of plasmids harbouring blaCTX-M-1 were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 17 publications
4
32
1
Order By: Relevance
“…Furthermore, the rifampicin resistance gene arr-3, and the aac(6′)Ib-cr gene, which confers resistance to both fluoroquinolones and aminoglycosides, were found in all four ST2179 isolates of this study (Table 1). Although we did not confirm resistance phenotypes by susceptibility testing, previous studies showed high accordance between resistance phenotype and genotype 20,21 . Multi-drug resistance, which is frequently observed in ESBL/pAmpC-EC 22,23 , is crucial for their selection and dissemination by the use of non-β-lactam antimicrobial agents and thus may help to explain the high prevalence of ESBL/pAmpC-EC in broilers even in the absence of cephalosporin use 24 .…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, the rifampicin resistance gene arr-3, and the aac(6′)Ib-cr gene, which confers resistance to both fluoroquinolones and aminoglycosides, were found in all four ST2179 isolates of this study (Table 1). Although we did not confirm resistance phenotypes by susceptibility testing, previous studies showed high accordance between resistance phenotype and genotype 20,21 . Multi-drug resistance, which is frequently observed in ESBL/pAmpC-EC 22,23 , is crucial for their selection and dissemination by the use of non-β-lactam antimicrobial agents and thus may help to explain the high prevalence of ESBL/pAmpC-EC in broilers even in the absence of cephalosporin use 24 .…”
Section: Resultscontrasting
confidence: 73%
“…The insertion of the module ISEcp1-bla CTX-M-1 into the shufflon region seems to be common for IncI1 plasmids belonging to pST3, as shown in previous studies identifying this plasmid type from various sources 46,[49][50][51] . A recent study reported identical bla CTX-M-1 -carrying IncI1 pST3 plasmids from chicken, chicken meat, and bloodstream infections in humans 21 . Furthermore, additional resistance genes, mainly tet(A) and sul2 (Table 1), were found on the IncI1bla CTX-M-1 plasmids and their co-localisation with bla CTX-M-1 has been described before 21,45 .…”
Section: Resultsmentioning
confidence: 96%
“…A recent study by Valcek et al on IncI1-pST3 and -pST7 plasmids showed that using combined long-read and short-read sequencing data improves the accuracy of a full plasmid analysis, e.g. of rearrangements [15]. All of studies used either gene presence/absence based or SNP based analysis, but not both, possibly missing subtle differences between various plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…Incompatibility group I1 (IncI1) plasmids of the plasmid sequence type (pST) 12 have been associated with the spread of blaCMY-2, the most common AmpC beta-lactamase gene [9][10][11]. Recent studies show that the sequence of IncI1 plasmids is highly conserved [12][13][14][15]. Most studies to date are based on short-read sequence data [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation